Análisis de factores para aumentar la eficacia de los convenios sociales entre las pequeñas compañías mineras formales y sus comunidades vinculadas en el Perú - Suárez García, Mijaíl Essenín (2021)
In this research, a study will be carried out on the problem of putting into operation social agreements between small mining companies and their related communities. A mixed investigation will be carried out in which the qualitative study will be appreciated through interviews and the quantitative study through surveys from a representative sample of the sector and subsector. The objective of this research is to improve the effectiveness of social agreements between small mining companies and their related communities to determine the influence of knowledge / experience of personnel and the impact of communication skills. The hypothesis refers to the condition in which if the knowledge / experience of the personnel and the communication capacity is improved, then the social agreements between the small mining companies and their communities will be improved.